Assessment of Insurance Cost of Religious historical and Cultural Monuments - Rimma Rygzynovna Afanasieva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article discusses the problems associated with the protection and evaluation of the St. Petersburg-monuments of architecture buildings, which are under state protection, with appropriate protection status - «a monument of history and culture». We also consider the technical issues be included in the market value of the property factor «historical reputation» with three classical approaches to evaluation - cost, income and comparative. Of particular interest is the formation of a project cost of insurance for the purpose of St. Isaac’s Cathedral, included in the list of UNESCO World Heritage sites. In the absence of a proper valuation of methodical maintenance of monuments article authors try to construct an algorithm and a procedure for determining the insurance value of St. Isaac’s Cathedral.